Bedside ultrasonography for the confirmation of nasogastric tube placement: agreement between nurse and physician - Silvia Fatima Ferraboli; Mariur Gomes Beghetto (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To evaluate the agreement between nurse and physician in verifying the positioning of the nasogastric tube by ultrasonography and describe the difficulties faced by nurse in performing the technique. Method Cross-sectional study conducted in 2021, including critical patients after nasogastric tube insertion who were independently evaluated by a nurse and physician, using bedside ultrasonography. The tube was considered adequately positioned when viewed in infradiaphragmatic location in the topography of the stomach. Results In the 30 peer evaluations there was almost perfect agreement (k = 0.93; 95%CI: 0.65 - 0.99). In only one case the nurse was uncertain about the positioning. Some difficulties were reported: abdominal distention (n=2), gas interposition (n=3) and patient movement during the exam (n=2). Conclusion A trained nurse obtained very similar results to those found by a physician in identifying the nasogastric tube placement by means of ultrasonography, suggesting a reproducible and safe technique.